Al-tavāṣil al-faʹʹāla`abir NLP va lughati al-jasad - Shaḥrūr, Laylá (Al-dar Al-arabiya lil`ulum nasherun, 2011)
It's about the effective communications...
Keywords: NLP : psykologia; sanaton viestintä : NLP; sosialinen vuorovaikutus : NLP